Identifikasi Ekspresi Glikokonjugat pada Jaringan Limfonodus Sapi Bali yang Terinfeksi Virus Penyakit Jembrana Secara Eksperimental - Oka Winaya, Ida Bagus; Ayu Mirah Adi, Anak Agung (Jurnal Veteriner; Vol 10 No 1 (2009), 2009)
The aim of this study is to compare glycoconjugate expression in the lymphonodes between bali cattleexperimentally infected with jembrana virus disease and non infected cattle. The biotinylated lectinsused in this study were Concavalia ensiformis (ConA), Arachis hypogaea (WGA), Triticum vulgaris (PNA),Ulex europeaus (UEA-1), and Sambucus nigra (SNA), respectively. The expression of lectin bindingglycoconjugate exhibit differences between the lymphonodes of infected and non infected cattle. Con A,WGA, and SNA were found be bound to lymphocytes whereas in infected cattle it was less intensive,repectively. More over, PNA and UEA were found strongly bound to the either lymphocytes of eitherinfected and non infected cattle.
Keywords: glycoconjugate, lymphonodes, lectin, bali cattle